Research of the Motivational Component of Professional Activity of Employees of the Security and Defense Sector - Fedorenko, Olena; Dotsenko, Victoria; Petruk, Oleh; Bedan, Viktoriia; Vikhtiuk, Andriy; Kudermina, Olena; Izbash, Svitlana (International Journal of Criminology and Sociology, 2021)
The paper presents a study of the characteristics of the professional motivation of security and defense workers and reveals the relationship between motivation and individual psychological qualities and people’s attitudes to various aspects of reality in police officers and servicemen. The logical relationship of correlations between work motivators and personality qualities and the attitude of servicemen and police officers to various aspects of reality is found, which will help the leader (psychologist) to increase efficiency. The article says that adequate and timely stimulation of activities based on personal qualities and attitudes to various aspects of the life of security and defense workers will prevent negative factors (development of emotional burnout, deviant behavior, negative mental states, etc.) and successfully correct them. The article aims to study the statistical motivation of security and defense workers and determine the relationship between motivation and individual psychological qualities and people’s attitudes to various aspects of reality in police officers and servicemen.